2010
DOI: 10.1037/a0016465
|View full text |Cite
|
Sign up to set email alerts
|

Does face inversion change spatial frequency tuning?

Abstract: The authors examined spatial frequency (SF) tuning of upright and inverted face identification using an SF variant of the Bubbles technique (F. Gosselin & P. G. Schyns, 2001). In Experiment 1, they validated the SF Bubbles technique in a plaid detection task. In Experiments 2a-c, the SFs used for identifying upright and inverted inner facial features were investigated. Although a clear inversion effect was present (mean accuracy was 24% higher and response times 455 ms shorter for upright faces), SF tunings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(117 citation statements)
references
References 81 publications
(182 reference statements)
9
107
1
Order By: Relevance
“…For example, two studies examined the spatial frequency bands used for face identification and found no differences between the upright and inverted conditions (Gaspar, Sekuler, & Bennett, 2008;Willenbockel et al, 2010). Also inconsistent with the holistic processing hypothesis, Gold, Mundy, and Tjan (2012) have shown that human observers' ability to identify a whole face is not superior to what is predicted by an optimal linear integration of information from individual features.…”
Section: Introductionmentioning
confidence: 93%
“…For example, two studies examined the spatial frequency bands used for face identification and found no differences between the upright and inverted conditions (Gaspar, Sekuler, & Bennett, 2008;Willenbockel et al, 2010). Also inconsistent with the holistic processing hypothesis, Gold, Mundy, and Tjan (2012) have shown that human observers' ability to identify a whole face is not superior to what is predicted by an optimal linear integration of information from individual features.…”
Section: Introductionmentioning
confidence: 93%
“…Gold et al, 1999;Näsänen, 1999;Willenbockel et al, 2010). Even more surprising, although face inversion profoundly disrupts low-SF-driven interactive face processing, several papers report that the magnitude of the FIE is equal across SF (Boutet et al, 2003;Gaspar et al, 2008a;Goffaux, 2008;Willenbockel et al, 2010). This divergent empirical evidence has led researchers to question the role of interactive face processing in face recognition (Konar et al, 2010).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Goffaux, 2009) does not coincide with SF best supporting the recognition of face identity (between 7 and 16 cpf; e.g. Gold et al, 1999;Näsänen, 1999;Willenbockel et al, 2010). Even more surprising, although face inversion profoundly disrupts low-SF-driven interactive face processing, several papers report that the magnitude of the FIE is equal across SF (Boutet et al, 2003;Gaspar et al, 2008a;Goffaux, 2008;Willenbockel et al, 2010).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations